Synthesis of Some New Heterocyclic Compounds Via Chalcone Derivatives - S. Al-Rawi, Muna (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The chalcones 1( a,b) were prepared by the reaction of 2- acetyl benzofuran with two aromatic aldehydes in the presence of alkaline media. These chalcones are used as starting material to obtain the desired heterocyclic: pyrazolin, isoxazoline, pyrimidinthion, pyrimidinone, cyclohexanone and indazole derivatives. The structure of newly synthesized heterocyclic compounds were established on the basis of their melting points, elemental analysis(C.H.N), FTIR and 1HMNR (for some of them) spectral data . The synthesized compounds have been screened for their antibacterial activities, they exhibited good antibacterial activity against Escherichia coli (G-) and Staphylococus aureus (G+) .